2021
DOI: 10.3346/jkms.2021.36.e184
|View full text |Cite
|
Sign up to set email alerts
|

Parental Mental Health and Children's Behaviors and Media Usage during COVID-19-Related School Closures

Abstract: Background Coronavirus disease 2019 (COVID-19) is different from previous disasters in that it continues to the present and has affected all aspects of family life. During epidemics, psychosocial support is not less important than infection control. During COVID-19-related school closures, prolonged partial closures of schools could have detrimental social and health consequences for children and may increase the burden on the family. Based on a community sample in Korea, this study identified par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
53
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 25 publications
(31 reference statements)
4
53
1
10
Order By: Relevance
“…In fact, the majority of children with autism spectrum disorder (ASD) had a higher probability of worsened behavioral symptoms during the pandemic than during the pre-COVID-19 era, and the need for professional support as perceived by parents was more for children with NDDs than for TDC 2 , 5 . Moreover, in a previous study, the prevalence of maternal depression increased especially in children with NDDs during the COVID-19 pandemic 6 , 7 , and maternal depressive state negatively interacted with changes in lifestyles and maladaptive behaviors of children with NDDs during the COVID-19 pandemic 1 , 3 5 , 8 . This negative interaction was observed between children with NDDs and their caregivers during ordinary times 9 , 10 and previous natural disasters prior to the COVID-19 pandemic 11 , and was even worse during emergency situations.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…In fact, the majority of children with autism spectrum disorder (ASD) had a higher probability of worsened behavioral symptoms during the pandemic than during the pre-COVID-19 era, and the need for professional support as perceived by parents was more for children with NDDs than for TDC 2 , 5 . Moreover, in a previous study, the prevalence of maternal depression increased especially in children with NDDs during the COVID-19 pandemic 6 , 7 , and maternal depressive state negatively interacted with changes in lifestyles and maladaptive behaviors of children with NDDs during the COVID-19 pandemic 1 , 3 5 , 8 . This negative interaction was observed between children with NDDs and their caregivers during ordinary times 9 , 10 and previous natural disasters prior to the COVID-19 pandemic 11 , and was even worse during emergency situations.…”
Section: Introductionmentioning
confidence: 78%
“…Moreover, previous research showed the prevalence of maternal depression increased, especially in parents’ of children with NDDs, during the COVID-19 pandemic 6 , 7 , and parents of children with ASD had lower levels of resilience and coping skills against overall stress, not just parenting stress 7 . Additionally, maternal depressive state also showed a negative interaction directly with children’s unhealthy lifestyles and maladaptive behaviors during the COVID-19 pandemic 1 , 8 . In previous follow-up studies, psychiatric disorders, especially depression, were also related to reduced QOL in the adult population, not just parents with NDDs exposed to natural disasters 15 , 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also explored the age differences in the association of maternal emotional status and child over-use of electronic devices, and suggested that the over-use of portable internet devices among young children deserved most attention. Second, up to now, a limited number of studies focused on child media exposure/screen time during the COVID-19 ( 49 , 50 ), but only school-age children (6–12 years) were included in these studies. Because younger children may be more susceptible to the effects of over-use of electronic devices on behavioral or physical development ( 51 , 52 ), and children under 6 years old also used the electronic devices (based on our study, 97.6% for the children of 3–6 years and 85.6% for the children under 3 years old), therefore, studies focusing on electronic-device use among children aged 0–6 years during the COVID-19 pandemic are important.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding the influence of parent-related variables, existing literature reports on a variety of concurrent risk factors during school closure. For instance, children were as well subjected to social disparities, food insecurities,or increased media usage, to name a few(Dunn et al, 2020; Hawrilenko et al, 2021;Kim et al, 2021;Van Lancker & Parolin, 2020). Taking other risk factors into account, negative psychosocial outcomes in schoolchildren are multifaceted and not entirely intertwined with parental characteristics.…”
mentioning
confidence: 99%